Holistic approach to anti-knock agents: A high-throughput screening of aniline-like compounds - Viayna, Antonio; Ghashghaei, Ouldouz; Vílchez, David; Estarellas, Carolina; López, Manuel; Gómez-Catalán, Jesús; Lavilla, Rodolfo; Delgado, Jesús; Luque, F. Javier (Fuel (Guildford), 2021)
•Assessment of antiknock compounds is needed in light of the new engine requirements.•A holistic approach is designed for high-throughput screening of aniline-like compounds.•Physicochemical factors, radical reactivity and environmental and toxicological risks are evaluated.•In some instances RON enhancements of 3 units have been found for gasoline EN-228 Efitec 98.•Few aniline derivatives are selected according to their impact on both RON changes and safety index. The increasing concerns about greenhouse gas emissions are encouraging the search for efficient combustion technologies for transportation. A valuable strategy consists of tailoring the properties of fuels through addition of additives that might increase the octane number subject to the classification, labeling and packaging regulation of fuel quality. In this context, we present an integrated approach involving a high-throughput screening that relies on selected physicochemical factors of aniline-like compounds, measurements of structural resemblance and susceptibility to participate in chemical reactions with radical species, in conjunction with production viability as well as environmental and toxicological risks. This process led to a final set of representative compounds that were chosen to explore their behavior as anti-knock additives. The suitability of these compounds was determined through assays performed to determine the impact on fuel volatility and RON booster efficiency in conjunction with a critical assessment of their eco/toxicological risk estimated by means of a safety index. This holistic strategy led to the identification of N-methyl-p-anisidine, N',N'-diethyl-2-methyl-p-phenylenediamine and N-nitroso-diphenylamine as promising anti-knock additives. This approach is proposed as an alternative strategy to the unsupervised experimental screening of fuel additives.